Dydaktyka przekładu literackiego w parze językowej polski–chiński. Zaplanowana seria przekładowa jako translatum i materiał badawczy .......... 169 - Wójcicka, Agnieszka (70 lat polonistyki Pekińskiego Uniwersytetu Języków Obcych: Dziedzictwo, rozwój, innowacje, 2025)
DIDACTICS OF LITERARY TRANSLATION IN THE POLISH-CHINESE LANGUAGE PAIR: A GUIDED TRANSLATION SERIES AS TRANSLATUM AND RESEARCH MATERIAL This research contributes to the study of poetry translation and offers new insights into the didactics of literary translation and glottodidactics. It is empirically grounded in the Polish-language poem W leśniczówce (In the Cottage, literally In the Forester’s Lodge) by Konstanty Ildefons Gałczyński, alongside fifteen Chinese translations and two intersemiotic transpositions produced by Chinese students of Polish as a foreign language. These works emerged from an original translation project developed and implemented within the Polish-Chinese Translation course at the Faculty of Polish and Classical Philology, Adam Mickiewicz University in Poznań, during the 2021/2022 academic year.To highlight the central aspects of the experiment, particular attention is given to renditions into Classical Chinese as well as into nonverbal sign systems (a dance interpretation and a musical arrangement). These translations serve as a valuable point of departure for reflecting on the diverse mechanisms and processes that arise at the intersection of languages and cultures.